Reduction of FeO Dissolved in Cao sio2-A12O3 Slags by Iron-Carbon Droplets - Yasushi Sawada (The Minerals, Metals and Materials Society, 1992)
An experimental investigation was carried out to study the rates of reduction of iron oxides dissolved in liquid Ca0-SO2-A203 slags by Fe-C droplets at temperatures ranging from 1325 OC to 1550 OC. The %FeO in the slag was varied from 5.5 to 18. Flash X-ray images were employed to observe the behavior of Fe-C droplets in the slags during the reactions and for determining the slag-gas-metal interfacial area. Effect of P205 in the slag and sulfur in the droplet was also investigated. The reduction rates were determined by measuring the volume of CO evolved as a function of time and the estimated slag-gas- metal interfacial area. The reduction rates have increased with increasing %FeO in the slag and the slag temperature. The experimentally established relationship between the reduction rates and FeO (wt%) in slag is given by